The association of tree species diversity and abundance with the soil edaphic factor in a largest tropical recreational forest of Terengganu, Peninsular Malaysia - Khairil Mahmud,; Khairulakwa H.,; Nur Fatihah H.N.,; Nornasuha Y.,; Khandaker M.M.,; Mohd Izuan Effendi Halmi,; Noor-Amalina R.,; Wan Juliana Wan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A study was conducted to investigate the association between tree species composition with soil edaphic factor in Chemerong Recreational Forest, the largest recreational forest in Terengganu, Peninsular Malaysia. Two types of forest were chosen which are riparian forest and inland forest. Four plots with the dimension of 50 m × 20 m each were established with two plots at each forest type with total study site of 0.4 ha. A total of 1158 trees (>1 cm diameter) from 263 species, 125 genus and 50 families were recorded. The higher species number was recorded in the inland forest with 175 species, 103 genus and 45 families compared to riparian plot with 154 species, 109 genera and 39 families. Lijndenia laurina was found to be the important species in the riparian forest with Important Value Index (IVi) of 5.22% while Mangifera caesia at the inland forest with 3.21%. The Shannon-Weiner diversity indexes (H’) was considered high in all two types of forest with 5.04 at the riparian forest and 5.14 at the inland forest. Sorenson’s community similarity coefficient (CCs) showed the tree species communities, between the two types of forest had low similarities with 0.38. A total 33 endemic species in Peninsular Malaysia were found at Chemerong Recreational Forest. Fifty-five species in this study were listed in the International Union for Conservation of Nature IUCN red list of threatened species 2019. Significant differences were found in phosphorus, electric conductivity, ammonium nitrate, moisture content and organic matter between these forests. Canonical Correspondence Analysis (CCA) showed less association between species composition with the physico-chemical characyeristics of soil in this study indicating the soil edaphic factor is not the main factor controlling the species distribution at this site.